City Size, Family Migration, and Gender Wage Gap: Evidence from Rural-Urban Migrants in China - Chunbing Xing; Xiaoyan Yuan; Junfu Zhang (Institute of Labor Economics (IZA), 2022)
Finding suitable employment in a city is more challenging for married than unmarried migrants. This paper provides empirical evidence that the denser and more diversified labor markets in large cities help alleviate the colocation problem of married couples. Using data from China, we show that the gender wage gap among married migrants is significantly smaller in larger cities, and this is mainly because large cities have higher employer and population densities. Large cities make married women more likely to be employed and to secure suitable jobs after family migration. We find no evidence for alternative explanations for the correlation between city size and married women's relative wages.
Keywords: J31; R12; R23; O15; 330; city size; family migration; colocation choice; gender gap